Facial asymmetry in subjects with Class III malocclusion - Kilic Nihat; Kilic Songül Comert; Catal Gülhan (Sciendo, 2023)
Facial skeletal asymmetries in Class III subjects seeking orthognathic surgery may complicate subsequent treatment.